Trend and Usage of Internet for Self Directed Learning in Phase I MBBS Students in an Urban Medical College: Observations and Challenges - Bhattacharyya, Swati; Roy, Suparna; Kar, Kaushik; Dasgupta, Anindya (Journal of College of Medical Sciences-Nepal, 2022)
Introduction GMR 2019 have suggested fixed hours of self-directed learning (SDL) for all subjects for helping the students to develop their learning skills and sense of responsibility for a better learning in future. Presently, the trend of SDL is becoming more e learning centric in comparison to use of text books with its consequent advantages and disadvantages. The present study aimed to analyze the challenges associated with this trend in the phase 1 MBBS students. Methods In an interventional educative study 203 phase 1 students from an urban medical college were assessed for an SDL based project on clinical aspects of the urea cycle at the end of the topic ammonia metabolism in Department of Biochemistry. Output from students were analysed for their trend for using resource materials, selection of relevant materials and originality of their inputs during the SDL process. Data obtained were analysed for their percentage distribution and difference of mean values as applicable. Results Out of 197 students who submitted their SDL projects in completed form, 61% students used internet information only, 20% used books only while 19% used both their resource materials. 32% of them could not use right key words for search and produced irrelevant materials in their topic. About 58% adopted copy and paste process without any change. Interestingly, the marks obtained by text book users were significantly higher than those using e resource materials. Conclusions The present study reveals that in spite of having a higher inclination to use e learning resources most of the students are yet to coordinate between their study topic & internet information. Moreover, the trend for copying without comprehension was found to be significantly higher among e learners. Hence, the investigators suggest that for proper use of SDL, guidance by expert faculties regarding how to search internet properly using appropriate keywords and how to comprehend the core information of the e-resources into their own language are necessary to make it a successful component of CBME.